Lexical Ambiguity Represented through Wordplay from @Epicdadjokes Instagram Posts - Hardiani, Yulia; Sihite, Meida Rabia; Harahap, Yunita Mutiara (EXCELLENCE: Journal of English and English Education, 2024)
This study is concerned with lexical ambiguity in the @epicdadjokes Instagram posts that is perceived stylistically. This research has three objectives: (1) to identify the forms of lexical ambiguity, (2) to interpret the meaning of lexical ambiguity represented through wordplay, and (3) to find out the effects of lexical ambiguity represented through wordplay on the meanings from posts of the account. This research employed a descriptive qualitative method. It was concerned with the posts from the @epicdadjokes Instagram Posts. The primary source of the data was the posts. The primary instrument was the researcher who acted as the data collector, data analyst and data interpreter. Then, the secondary instrument was the data sheet. In collecting the data, she selected the data, categorize and classified the data into three data sheets. In analyzing the data, she identified the data into the categorizations, and interpreted each datum based on the theories. The findings of the research show there are homonymy (83.33%) and polysemy (16.67%). Meanwhile, among the three sub-types of homonymy, only two of them occur, absolute homonymy (37.50%) and homophone (45.83%). The absent type is homograph. Then, there are three types of wordplay that occur in the posts i.e. Homonymic pun (25.00%), homophonic pun (29.17%), and the recursive pun (45.83%). Meanwhile, homographic pun, compound pun and visual pun does not occur. Finally, the two effects of lexical ambiguity are humorous (83.4%) and ironic effects (16.6%).